Thrombin generation and low-molecular-weight heparin prophylaxis in pregnant women with thrombophilia - Selmeczi, Anna; Roach, Rachel E. J.; Móré, Csaba; Batta, Zoltán; Hársfalvi, Jolán; Bom van der, Johanna G.; Boda, Zoltán; Oláh, Zsolt (Thrombosis and Haemostasis, 2015)
Pregnancy is associated with increased risk of venous thromboembolism, especially in the presence of thrombophilia. However, there is no consensus on the optimal approach for thromboprophylaxis in this population. Recent evidence suggests that thrombin generation correlates with the overall procoagulant state of the plasma. Our aim was to evaluate thrombin generation in a prospective cohort of thrombophilic pregnant women, and investigate the effectiveness of low-molecular- weight heparin (LMWH) prophylaxis in pregnancy. Women with severe (n=8), mild (n=47) and no (n=15) thrombophilia were followed throughout their pregnancies. Thrombin generation was evaluated in each trimester as well as five days and eight weeks postpartum (as a reference category). In women undergoing LMWH prophylaxis, thrombin generation and anti-Factor-Xa activity were measured just before and 4 hours after administration (peak effect). Thrombin generation was determined using Technothrombin TGA assay system. For the analysis, median peak thrombin and endogenous thrombin potential were used. Peak thrombin and endogenous thrombin potential were increased during pregnancy compared to the non-pregnant state with the highest results in the severe thrombophilia group. In women receiving LMWH prophylaxis a decrease was observed in thrombin generation at peak effect but over the progression of pregnancy the extent of this decrease reduced in a stepwise fashion. Our results show that thrombin generation demonstrates the hypercoagulable state in thrombophilic pregnancies. In addition, we found the effect of LMWH prophylaxis to progressively decrease with advancing stages of pregnancy.
Keywords: Thrombophilia; pregnancy; LMWH prophylaxis; thrombin generation